Publications and new products (Journal of EAHIL, 2017)
Dear Colleagues,Services provided by librarians to clinicians have been shown to be effective in saving time for health professionals andproviding relevant information for decision-making. Patients’ length of stay was reduced when clinicians requestedliterature searches related to a patient's case (L. Perrier et al., J Am Med Inform Assoc. 2014 May 28).Moreover, librarians have become more involved in developing high quality systematic reviews (P. Cruse and S.Protzko. Med Ref Serv Q. 2014;33:327).A study compared Wikipedia articles on the most costly medical conditions with standard, evidence-based, peerreviewedsources. The conclusion is that caution should be used when using Wikipedia to answer questions regardingpatient care (R.T. Hasty et al. J Am Osteopath Assoc. 2014;14:368).